Unknown ingestion of dentures – Review and description of a case report. (February 2022) - Salvador, David; Pratas, Nuno; Capote, Hugo
Abstract: Background: Foreign-body ingestion is a common occurrence in the Emergency Department (ED) and numerous types of objects have been implicated. Most of the foreign bodies pass through the GI system without any lesion but there's always a risk of impaction and perforation requiring surgery. The aim of the article and clinical case described is to provide a brief review of the diagnosis and management of foreign body ingestion. With this case report, the author raises awareness to the fact that the diagnostic is often elusive since even mentally capable patients might not notice or refer about ingestion of foreign bodies, especially dentures. Case presentation: 52-year-old female patient who presents to the ER with sudden onset of generalized abdominal pain localizing to the right lower quadrant with no history of foreign body ingestion. Clinically with signs of peritonism localised to the RLQ. Diagnosis of impaction by a foreign body ingestion was made with CT scan and clearly identified with 3D reconstruction of the CT scan. Proposed for urgent laparoscopy to remove FB and prevent perforation. However, minimal access surgery was unfeasible and even the laparotomy was difficulted by previous abdominal wall repair. Even so, the FB was retrieved after enterotomy and both the surgery and post op period recovery were uneventful. Discussion: The clinical presentation of an impacted/perforated foreign body in the bowel is not always straightforward, often simulating other acute abdominal urgencies such as appendicitis and diverticulitis. The most valuable method to locate the FB's and diagnose complications is the CT scan. The mainstay of management is the surgical removal of the foreign body in the bowel through minimal access surgery (laparoscopy) or laparotomy, if necessary. Conclusion: Even though foreign body ingestion is a very common phenomenon, most of the time is harmless and no medical care is necessary. However, when it does occur, the diagnosis of a related complication may be elusive when no suspicion is brought on by clinical history. When presented with a patient with unexplained abdominal pain, the ingestion of foreign object should be present in the differential diagnosis. Minimal Invasive surgical treatment is first option, but laparotomy might prove to be necessary. Highlights: Case report and brief review. Unsuspected foreign body ingestion in a mentally capable adult. Abdominal pain due to impaction in small bowel. Abdominal cavity CT scan imaging. Converted Laparoscopy to Laparotomy with previous abdominal wall mesh repair.